Recent Advances in InAs Quantum Dot Lasers Grown on On‐Axis (001) Silicon by Molecular Beam Epitaxy. Issue 1 (28th December 2018) - Jung, Daehwan; Norman, Justin; Wan, Yating; Liu, Songtao; Herrick, Robert; Selvidge, Jennifer; Mukherjee, Kunal; Gossard, Arthur C.; Bowers, John E.
Abstract : Recent advances in InAs quantum dot (QD) lasers epitaxially grown on on‐axis (001) silicon are reported. Fabry‐Perot QD lasers show a CW threshold current of 4.8 mA at 20 °C, extrapolated laser lifetimes more than 10 million hours when aged at 35 °C, NRZ direct modulation up to 12 Gbps, and low linewidth enhancement factor of ≈0.1. Ultra‐small microring QD lasers reveal a CW threshold of 0.5 mA and single‐section mode‐locked QD lasers demonstrate 490 fs ultra‐short pulses at a 31 GHz repetition frequency. Possible ways to grow QD lasers on Si without misfit dislocations in active region are considered in order to further enhance reliability of QD Si lasers at high aging temperature and aging current density. Abstract : Recent advances in InAs quantum dot (QD) lasers epitaxially grown on on‐axis (001) silicon are reported. Fabry‐Perot QD lasers show a CW threshold current of 4.8 mA at 20 °C, extrapolated laser lifetimes more than 10 million hours when aged at 35 °C, NRZ direct modulation up to 12 Gbps, and low linewidth enhancement factor of ≈0.1.